Two-phase treatment of class II malocclusion in young growing patient - U S Krishna Nayak; Varun Goyal; Nikhil Malviya (Wolters Kluwer Medknow Publications, 2011)
The use of functional jaw orthopedics, at the correct time during growth, can ultimately result in malocclusion patients achieving a broad beautiful smile, an excellent functional occlusion, a full face with a beautiful jaw line and lateral profile. Following is a case report of a young growing individual with mandibular retrognathia. Treatment was planned in two stages with the use of twin block during the first phase for correction of skeletal malocclusion and forward positioning of the mandible, followed by the second phase of fixed pre-adjusted edgewise orthodontic appliance for camouflaging the remaining skeletal discrepancy and achieving a stable harmonious occlusion.